Pengelolaan zakat yang transparan: Memastikan dana zakat digunakan dengan tepat - Nisa, Fadhila Auliya (Maliki Interdisciplinary Journal, 2024)
Distribution of zakat in Indonesia looks quite good. However, who would have thought that even though it is only about the distribution of zakat, it does not rule out the possibility that such distribution occurs and is only aimed at certain parties. Even though the Indonesian people are very enthusiastic in participating in these activities. Zakat in the form of funds is widely used by Indonesian people to meet their needs. It is not uncommon for the good fortune that comes from zakat in various forms to help people overcome the economic problems they are facing. Based on human nature which has a consumerist spirit, there are many expectations from society regarding zakat so that it can be distributed and delivered to people who are entitled and deserve to receive it. Like zakat fitrah in the form of rice, this really helps people fulfill the consumerist spirit within them so that they can carry out their activities productively and optimally. When zakat funds can be distributed correctly and optimally, the community can experience prosperity with the help of these funds. Indirectly, zakat funds can improve people’s welfare if they are channeled according to the right targets. However, it is undeniable that there are still some mistakes or even deliberate distribution of these funds so that people who are supposed to get their rights are diverted to parties who do not have their rights. This can be a feeling of disappointment for the people who experience it. The reason is, most of them hope that funds from zakat can help them ease their burdens in the future.